Experımental determination of the breakaway force of working rolls when processing semi-finished products - Nabiev Ayder; Tsoy Gerasim; Bahadirov Gayrat; Umarov Abdurasul; Rakhimov Furkat; Musirov Makhmarajab (BIO Web of Conferences, 2024)
The effect of varying the number of layers of a semi-finished product, that is, its thickness, and the pressing force between the working rolls on the breakaway force of a multi-layer package of semi-finished products is experimentally investigated in the article. The dependence of the required breakaway force of the working rolls on the change in the number of layers of semi-finished products supplied for mechanical processing between the working rolls at different pressure forces was experimentally determined. The values of the required breakaway force for the working rolls at the established values of the pressing force of the working rolls for packages consisting of five, ten, and sixteen layers of semi-finished products were obtained.